Evaluation of Bacterial Contamination of Baladia cheese sold in The local markets of Hama city (Journal of Hama University, 2024)
This study aimed to evaluate the bacteriological contamination of local cheese (Baladia chesse) and its compliance with the health requirements for bacteria, so 38 cheese samples were collected randomly from different places in the local markets of Hama during the month of June 2022 AD, through which bacterial tests were conducted, which included (Total Viable Bacterial count, total coliform count, E.coli count, Staphylococcus aureus count and detection of Salmonella).The results of the research showed a high content of bacteria in baladia cheese, as it reached an average of (2.89 x 107, 1.35 x 105 and 5.67 x 103) CFU/1 g in each of the total number of aerobic bacteria, the total number of Coliform bacteria and the number of E.coli, respectively, while the percentage of positive samples Staphylococcus aureus was 65.7% of the samples, as its average number in positive samples was 1.7 x 102 CFU/1g, while the percentage of the Bacillus salmonella reached 5.26%.The study also showed that this cheese did not have the minimum requirement to be accepted in the Syrian standard specifications, as the health violation rate reached (76.31%, 12% and 5.26%) for coliform, Staphylococcus aureus and Salmonella respectively